Health workers’ knowledge, attitudes, and perceptions concerning MRSA at two hospitals in Ghana - Kugbeadzor, Rose MAJ; Kotey, Fleischer CN; Donkor, Eric S (The Journal of Infection in Developing Countries, 2025)
Introduction: This study assessed the knowledge, attitudes, and perceptions (KAPs) regarding methicillin-resistant Staphylococcus aureus (MRSA) among healthcare workers at the Ho Teaching Hospital and Ho Municipal Hospital in Ghana. Methodology: This cross-sectional study involved 157 healthcare workers whose KAPs were assessed using a standard questionnaire. Results: The overall knowledge of the respondents about MRSA was sufficient (mean score = 0.58 ± 0.15). Medical doctors demonstrated the highest knowledge (mean score = 0.80), but their knowledge on the challenges in implementing effective preventive measures against MRSA acquisition, risk factors for transmission, and predominant mode of transmission were poor (mean scores = 0.18–0.37). The respondents’ MRSA-related attitudes (mean score = 2.74 ± 0.31) and perceptions (mean score = 2.88 ± 0.29) were generally positive, with the highest scores recorded among laboratory staff (n = 10) (mean attitude score = 2.92 ± 0.25; mean perception score = 3.06 ± 0.24). The factors that influenced MRSA KAPs included age group (knowledge [p < 0.001]), educational level (knowledge [p < 0.001], and perception [p = 0.044]), and healthcare worker designation (knowledge [p = 0.044]). Nurses were six times more likely to have good knowledge about MRSA compared to pharmacy staff (OR = 6.05, p = 0.045). Conclusions: The respondents had adequate knowledge, and positive MRSA-related attitudes and perceptions, although some knowledge deficits were identified. These knowledge deficiencies can be addressed during the design of educational programs on MRSA, and by increasing research on KAPs regarding MRSA, among key stakeholders in healthcare, particularly, in Ghana.